2012
DOI: 10.1016/j.cmet.2012.01.008
|View full text |Cite
|
Sign up to set email alerts
|

The Vascular Endothelium of the Adipose Tissue Gives Rise to Both White and Brown Fat Cells

Abstract: Summary Adipose tissue expansion involves the enlargement of existing adipocytes, the formation of new cells from committed preadipocytes, and the coordinated development of the tissue vascular network. Here we find that murine endothelial cells (EC) of classic white and brown fat depots share ultrastructural characteristics with pericytes, which are pluripotent and can potentially give rise to preadipocytes. Lineage tracing experiments using the VE-cadherin promoter reveal localization of reporter genes in EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
250
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(268 citation statements)
references
References 37 publications
12
250
2
1
Order By: Relevance
“…Recently, work by Tran and colleagues reported that murine endothelial cells (ECs) of classic white and brown fat depots share ultrastructural characteristics with pericytes, a stem celllike population that can potentially differentiate into preadipocytes. Lineage tracing experiment using VE-cadherin promoter revealed localisation of reporter genes in not only pre-adipocytes and adipocytes of WAT and BAT depots but also in ECs (Tran et al 2012). Taken together, these results support an endothelial origin of murine and human adipocytes (Fig.…”
Section: Bat Precursors In Adult Mice: Endothelial and Other Originssupporting
confidence: 74%
“…Recently, work by Tran and colleagues reported that murine endothelial cells (ECs) of classic white and brown fat depots share ultrastructural characteristics with pericytes, a stem celllike population that can potentially differentiate into preadipocytes. Lineage tracing experiment using VE-cadherin promoter revealed localisation of reporter genes in not only pre-adipocytes and adipocytes of WAT and BAT depots but also in ECs (Tran et al 2012). Taken together, these results support an endothelial origin of murine and human adipocytes (Fig.…”
Section: Bat Precursors In Adult Mice: Endothelial and Other Originssupporting
confidence: 74%
“…This is a highly significant finding given that HO is perhaps most commonly observed in skeletal muscle [90]. A derivational link between endothelial cells and adipocytes has also been identified, with capillary sprouts present in adipose tissue being found to express both endothelial (VE-Cadherin) and pre-adipocyte (Zfp423) markers [91]. Furthermore, the formation and expansion of adipose tissue is reliant on the presence of a rich capillary network.…”
Section: Endoderm Endothelial Cellsmentioning
confidence: 83%
“…A previous study on ATMs in lean mice [11] reported that M2 ATMs reside between adipocytes and occasionally associated with blood vessels, which is supported by the present study. More recently, it was shown that some adipocytes originate from fetal vascular endothelium [36] and ASCs may be physiological progenitors for both adipocytes and vascular endothelial cells [37], which may also suggest a close relationship among CD206 + ATMs, adipocytes, and vascular cells.…”
Section: Cd34-positive Adipose-resident Macrophagesmentioning
confidence: 99%